Trading Volume Activity, January Effect, and Stock Splits on Stock Market Returns - Zalisman Rahmadan; Yuliusman Yuliusman; Rita Friyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to explore and assess the correlation between Trading Volume Activity, Stock Splits, and the January Effect on Stock Market Returns. The study was carried out at technology sector companies listed on the Indonesia Stock Exchange (IDX). Nineteen sets of firm data were selected for analysis, each consisting of observations covering two years. The process of choosing data employed a purposive sampling technique, which involved the application of three specific criteria. The data underwent examination using Partial Least Squares Structural Equation Modeling (PLS-SEM) technique with SmartPLS 3.2.9 application. The study's findings indicate no significant connection between trading volume activity on stock market returns. However, it is observed that stock splits and the occurrence of January affect the impact on stock market returns.